722 Inhibition of integrin avß8-Mediated TGF-ß activation with C6D4 provides improved potency and selectivity vs general TGF-ß inhibitors for cancer immunotherapy. (9th November 2020) - Seed, Robert; Nishimura, Stephen
Abstract : Background: TGF-ß plays a key role in immune evasion as a critical regulator of both innate and adaptive tumor immunity and promotes broad immunosuppressive effects on numerous inflammatory cell subpopulations ultimately resulting in tumor immune tolerance and evasion. 1 It has also been implicated in resistance to immune checkpoint therapies, and additive or synergistic effects of dual TGF-ß and PD-1 inhibition has been reported. 2 3 A number of TGF-ß inhibitors are in clinical development with different modes of action. Most protein-based inhibitors are designed to block diffusible TGF-ß from interacting with its proximal signaling receptor TGF-ßR2 and includes monoclonal antibodies (Mabs) and receptor traps. This investigation compares inhibition of TGF-ß by a number of inhibitors and the integrin avß8 (C6D4) to assess their relative potential as cancer therapeutics. Methods: No reporter system currently exists to investigate the mechanistic basis of cell-intrinsic TGF-ß activation, whereby the L-TGF-ß presenting cell is also the cell that responds toTGF-ß signaling (figure 1). To build a cell-intrinsic TGF-ß activation system, TMLC cells were stably transfected with wild-type (WT) TGF-ß. Without co-transfecting GARP, TMLC do not present L-TGF-ß on their cell surface. When co-transfected with TGF-ß and GARP, high levels of cell surface expression of L-TGF-ß are detected. Additionally, to build a cell-intrinsic TGF-ß activation system which express a non-releasable form of TGF-ß, we mutated the L-TGF-ß furin cleavage site (R249A) and similarly expressed the L-TGF-ß(R249A)/GARP complex on the surface of TGF-ß reporter cells (TMLC). These cell-intrinsic TGF-ß activation systems were used to assess the relative abilities of Mabs avß8, TGF-ß, TGF-ßR2, GARP or TGF-ßR2 receptor trap to inhibit avß8-mediated TGF-ß activation. Results avß8 exhibited superior inhibitory activity compared with other TGF-ß inhibitors, which was similar in both diffusible and non-diffusible models (figure 2). The biologic relevance of these finding was confirmed using CD4+ T-cells in place of the reporter cells where TGF-ß-dependent Treg generation was almost completely blocked by avß8 but was poorly inhibited by the other TGF-ß inhibitors. Conclusions: In this study avß8 exhibited dramatic TGF-ß inhibitory activity compared with a wide range of inhibitors in development. Because integrin avß8 may direct TGF-ß signaling from within its latent complex, this may offer an advantage for target specificity and avoid the challenges faced by non-specific TGF-ß inhibitors. These findings characterize avß8 as a novel and potent immunotherapy drug for further clinical investigation. Trial Registration: NA Ethics Approval: NA References: Batlle E, Massagué J. Transforming growth factor-ß signaling in immunity and cancer. Immunity . 2019;50(4):924–940. Tauriello DVF, Palomo-Ponce S, Stork D, et al. TGFß drives immune evasion in genetically reconstituted colon cancer metastasis. Nature 2018;554(7693):538–543. Mariathasan S, Turley SJ, Nickles D, et al. TGFß attenuates tumour response to PD-L1 blockade by contributing to exclusion of T cells. Nature 2018;554(7693):544–548.